Implementasi Pasal 53 Undang-Undang Nomor 40 Tahun 2014 Tentang Perasuransian (Studi Komparatif Mekanisme Penjaminan Oleh Lembaga Penjamin Simpanan) - Wardhana, Ardiyanto (Green Publisher Indonesia, 2025)
Insurance Companies in Indonesia that have business permits to operate in Indonesia in 2017 have reached 391 companies consisting of 152 Insurance and Reinsurance Companies and 239 Insurance Business Support Companies (excluding Actuarial consultants and Insurance Agents). The Insurance and Reinsurance Companies consist of 61 Life Insurance Companies, 79 General Insurance Companies, 7 Reinsurance Companies, 2 Social Security Program Organizing Agencies and 3 Compulsory Insurance Organizing Companies. With the rapid development of insurance companies in Indonesia, the author wants to research the deposit guarantee for insurance customers who deposit their assets with insurance companies, this is related to the guarantee mechanism for insurance policy holders, which is mandated by Article 53 of Law Number 40 of 2014 concerning Insurance. The approach method used is a normative juridical approach such as a conceptualization approach and a statutory and regulatory approach which will also be supported by a comparative approach. Analysis of the legal materials used by the author was carried out by means of qualitative description, namely legal materials obtained from library research which were compiled systematically, researched and studied in their entirety. This legal writing will use comparative analysis techniques. The research results show that the implementation of article 53 of Law Number 40 of 2014 has not yet been implemented, and the Deposit Insurance Agency is really needed.